2016
DOI: 10.1071/an141007
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen balance in Holstein steers grazing winter oats: effect of nitrogen fertilisation

Abstract: The present study evaluated the effect of nitrogen (N) fertilisation of winter oats on whole-animal N balance (N intake, N excretion in urine and faeces, N retention), partition of urinary N (purine-N derivatives and urea-N) and average daily gain (ADG) in grazing steers. The experimental area was divided in two plots (10 steers/plot), and samples were obtained in two periods (one plot/period).The experimental area was divided in two plots, and each plot in 10 strips. Twenty Holstein steers (161.3 ± 7 kg of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Retained nitrogen values (average of 62.28 g/day-Table 4) can be used to estimate the average daily gain in live weight (kg) of the animals [39]. Considering that approximately 750 and 250 g/ kg of meat is water and protein, respectively, and assuming a N to CP ratio of 6.25 (i.e., adopting a body protein N content of 160 g/kg), this implies that the estimated average daily weight gain for steers in both treatments in the present study was approximately 1560 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…Retained nitrogen values (average of 62.28 g/day-Table 4) can be used to estimate the average daily gain in live weight (kg) of the animals [39]. Considering that approximately 750 and 250 g/ kg of meat is water and protein, respectively, and assuming a N to CP ratio of 6.25 (i.e., adopting a body protein N content of 160 g/kg), this implies that the estimated average daily weight gain for steers in both treatments in the present study was approximately 1560 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…In beef cattle, dietary N is generally either partitioned into tissues or excreted in faeces and urine . From a recent summary of published N balance studies on beef cattle offered high and low CP diets, Sánchez Chopa, Nadin, Agnelli, Trindade, and Gonda (2016) concluded that the effect of increased N intake on N-use efficiency was equivocal, with increases and decreases in efficiency observed across experiments. Compared to (lactating) dairy cows (Huhtanen, Nousiainen, Rinne, Kytölä, & Khalili, 2008;Kebreab, Strathe, Fadel, Moraes, & France, 2010;Warner et al, 2015;Whelan et al, 2017), there is much less understood about the relationships between beef cattle nutrition and N excretion (Johnson, Reed, & Kebreab, 2016;Waldrip, Todd, & Cole, 2013), and even less so in relation to beef cattle offered fresh grass (Sánchez Chopa et al, 2016).…”
mentioning
confidence: 99%